Therapeutic novelties in migraine: new drugs, new hope? - Thien Phu Do; Song Guo; Messoud Ashina (The Journal of Headache and Pain, 2019)
Abstract Background In the past decade, migraine research has identified novel drug targets. In this review, we discuss recent data on emerging anti-migraine therapies. Main body The development of ditans, gepants and anti-calcitonin gene-related peptide monoclonal antibodies for the treatment of migraine is one of the greatest advances in the migraine field. Lasmiditan, rimegepant and ubrogepant will extend our therapeutic armamentarium for managing acute migraine attacks when triptans are not effective or contraindicated due to cardiovascular disorders. The monoclonal antibodies are migraine specific prophylactic drugs with high responder rates and favorable adverse event profiles. Furthermore, they offer convenient treatment regimens of 4- or 12-week intervals. Conclusion Collectively, novel migraine therapies represent a major progress in migraine treatment and will undoubtedly transform headache medicine.